SIMULATION OF SOLAR CHIMNEY POWER PLANT WITH AN EXTERNAL HEAT SOURCE - ., AZEEMUDDIN (2013)
The Solar Chimney Power Plant is a power generating facility. It produces electricity by harnessing the energy from the sun into kinetic energy of air inside a collector. Its power to size ratio is very small. The plant commonly does not deliver significant output during the night hours. However, many studies have suggested its operation during night with an addition of facilities. The current research adopts the conversion of waste to energy policy using exhaust gases to enable the continuous plant operation and increase solar chimney power plant performance